2005
DOI: 10.17305/bjbms.2005.3280
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy in Orthopaedic Diseases

Abstract: The application of extracorporeal shock wave therapy (ESWT) as a treatment for different orthopaedic conditions has experienced a rapid increase over the last several years. However the mechanism of action and the therapeutic effect is not clear. The aim of this study was to review the literature about the efficacy of ESWT in the treatment of plantar fasciitis, lateral epicondylitis, shoulder painful disorders and non-union fractures. Only randomized controlled studies published in the last 5 years were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21] ESWT is an emerging method for improving the healing of long bone fractures in human subjects and experimental animals. [22][23][24][25] However, little research has been conducted to examine the effect of ESWT on bone formation in distracted bone tissue. 26 In this study, the bone mineral density of the distracted mandible was analyzed using dual-energy X-ray absorptiometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21] ESWT is an emerging method for improving the healing of long bone fractures in human subjects and experimental animals. [22][23][24][25] However, little research has been conducted to examine the effect of ESWT on bone formation in distracted bone tissue. 26 In this study, the bone mineral density of the distracted mandible was analyzed using dual-energy X-ray absorptiometer.…”
Section: Discussionmentioning
confidence: 99%
“…ESWT is an emerging noninvasive modality for the treatment of musculoskeletal disorders such as nonunion of a long bone fracture, lateral epicondylitis of the elbow, plantar fasciitis, and calcifying tendonitis. [22][23][24][25][26][27] In experimental animal models, ESWT enhanced the healing of long bone fractures by increasing cell differentiation and neovascularization. We have previously demonstrated that ESWT increases the callus size and biomechanical properties of bone tissue in long bone fractures in the rabbit.…”
mentioning
confidence: 99%
“…19 On the other hand, some reviews report that controlled randomized trials of ESWT did not result in significant improvement. 24 For treatment of Achilles tendinopathy, ESWT also can be considered, but we shall pay more attention to the complications that may be induced because of the weight bearing of the whole body. Some researchers claim that tendinopathy improves by at least 1 year after treatment without adverse effects, 25 but they exclude the case of tendon tear at first.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some reviews report that controlled randomized trials of ESWT did not result in significant improvement 24. For treatment of Achilles tendinopathy, ESWT also can be considered, but we shall pay more attention to the complications that may be induced because of the weight bearing of the whole body.…”
Section: Discussionmentioning
confidence: 99%